Method comparison and overview of refractive measurements in children: implications for myopia management - Lihua Li; Arne Ohlendorf; Siegfried Wahl; Jonas Müller; Xiaoqin Chen (BMJ Open Ophthalmology)
Objective This study investigated the agreement between objective wavefront-based refraction and subjective refraction in myopic children. It also assessed the impact of cyclopentolate and refraction levels on the agreement.Methods A total of 84 eyes of myopic children aged 6–13 years were included in the analysis. Non-cycloplegic and cycloplegic objective wavefront-based refraction were determined and cycloplegic subjective refraction was performed for each participant. The data were converted into spherical equivalent, J0 and J45, and Bland-Altman plots were used to analyse the agreement between methods.Results Linear functions were used to determine the dependency between the central myopic refractive error and the difference between the method of refraction (=bias). The influence of central myopia was not clinically relevant when analysing the agreement between wavefront results with and without cyclopentolate (comparison 1). The bias for wavefront-based minus subjective spherical equivalent refraction (comparison 2) was ≤−0.50 D (95% limits of agreement −0.010 D to −1.00 D) for myopia of −4.55 D and higher when cycloplegia was used (p<0.05). When no cyclopentolate was used for the wavefront-based refraction (comparison 3), the bias of −0.50 D (95% limits of agreement −0.020 D to −0.97 D) was already reached at a myopic error of −2.97 D. Both astigmatic components showed no clinically relevant bias.Conclusion The spherical equivalent, measured without cycloplegic agents, led to more myopic measurements when wavefront-based refraction was used. The observed bias increased with the amount of myopic refractive error for comparisons 2 and 3, which needs to be considered when interpreting wavefront-refraction data.Trial registration number NCT05288335.